Public pensions and low income dynamics in Canada - Mayssun el Attar; Raquel Fonseca (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
This paper focuses on individuals over 50 and shows that considering persistence and low income dynamics is essential to understanding poverty. We use administrative data for Canada from the Longitudinal and International Study of Adults (LISA). The paper shows that poverty for seniors is highly persistent and strongly depends on lifetime earnings. We show that beginning to receive a public pension implies a higher probability of exit from poverty. Public pensions thereby help to explain the lower overall incidence of poverty among the elderly. These results are confirmed in a dynamic probit model, which allows to control for individuals' unobserved heterogeneity and state dependence. While public pensions do not eliminate poverty among older adults, they help to alleviate it by reducing persistence and increasing exit for those who are most at risk.
Keywords: H55; J26; I32; 330; low-income; elderly; poverty dynamics; Canadian public pensions